Book Review of Is the Bangladesh Paradox Sustainable? The Institutional Diagnostic Project - Abdur Rahman (Muslim Politics Review, 2025)
The book Is the Bangladesh Paradox Sustainable? The Institutional Diagnostic Project, edited by Selim Raihan, François Bourguignon, and Umar Salam, delves into the puzzling question of how Bangladesh has managed to achieve sustained economic growth and social progress despite weak formal institutions and governance structures. The volume examines the "Bangladesh paradox" through a mix of empirical case studies and theoretical insights, highlighting that informal arrangements and sector-specific elite bargains have played a crucial role in the country’s development. The book challenges dominant theories of political economy, particularly the claim by Acemoglu and Robinson that inclusive institutions are necessary for development. The volume further explores key sectors such as the RMG industry, banking, taxation, land management, and the judiciar for understanding how adaptive governance mechanisms have compensated for institutional fragility. Despite Bangladesh's success, the book warns of the risks posed by rising inequality, climate change, and elite capture, suggesting that while informal institutions can sustain growth temporarily, they may not be sufficient in the long term. Overall, the book provides valuable insights for both scholars and policymakers on the complexities of development in Bangladesh.